A probe into the citation patterns of high-quality and high-impact publications - Jiang, Li; Ye, Fred Y.; Li, Jiang; Ye, Fred Y. (Malaysian Journal of Library and Information Science, 2017)
Li, J., & Ye, F. Y. (2014). A probe into the citation patterns of high-quality and high-impact publications. Malaysian Journal of Library & Information Science, Vol.19, no. 2: 17-33. Enlightened by Avramescu’s studies, we classified the citation patterns of high-quality and highimpact publicationsinto five mathematical types: lognormal type, exponential-type, polynomialtype, wave-type and sleeping-beauty. Based on practical datasets of high-quality and high-impact publications, the five types of citation patterns are fitted well at statistical level. The results reveal that high-quality publications usually appear irregular citation curves (wave-type and sleepingbeauty) and high-impact publications tend to show regular ones (lognormal-type, exponential-type and polynomial-type).